1996
DOI: 10.1002/(sici)1097-0045(199601)28:1<32::aid-pros5>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous vs. intraprostatic administration of N-methyl-N-nitrosourea to induce prostate cancer in rats

Abstract: To develop an improved model of human prostate cancer, 16‐wk‐old Wistar rats were treated orally for 18 days with the antiandrogen, flutamide (50 mg/kg body weight[BW]/day), weight followed by 3 days of s.c. testosterone (100 mg/kg BW). These were the only treatments the control animals received (Group 1, n = 10). On the day after the third testosterone injection, N‐methyl‐N‐nitorsourea (MNU) was administered via the tail vein at a dose of 50 mg/kg BW (Groups 2, n = 40 and 3, n = 20); in some rats, a second do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…wiley.com.] other carcinogenic agents [8,30,31]. The lesions observed were histologically similar to those described as atypical hyperplasia induced in rats by treatment with phenylephrine [32].…”
Section: Discussionsupporting
confidence: 69%
“…wiley.com.] other carcinogenic agents [8,30,31]. The lesions observed were histologically similar to those described as atypical hyperplasia induced in rats by treatment with phenylephrine [32].…”
Section: Discussionsupporting
confidence: 69%
“…This study con®rmed that a high proportion of prostate carcinomas induced in rats by the direct-acting methylating carcinogen MNU and subsequent chronic testosterone treatment carried the activating G 35 3 A mutation in the Ki-ras proto-oncogene observed in previous studies, but no mutations were detected in codon 12 of the Ha-ras gene [17,19]. This study further demonstrated that frequency of the Ki-ras mutation was similar in tumors induced in different rat strains, regardless of the substantial differences in sensitivity among these strains to the induction of prostate cancer by MNU and testosterone.…”
Section: Discussionsupporting
confidence: 74%
“…We previously reported that approximately 75% of prostate carcinomas induced in Wistar rats by MNU and subsequent chronic testosterone treatment carry an activating G 35 3 A mutation at the second position of codon 12 of the Ki-ras proto-oncogene [17], which was con®rmed by Schleicher et al [19]. We hypothesized that there are at least two molecular pathways of tumor induction by MNU in the rat prostate, the predominant one of which involves activation of the Ki-ras protooncogene [17].…”
Section: Introductionmentioning
confidence: 81%
“…Cancer developed commonly in Wistar rats that were treated by sequential chemical castration, stimulation, and MNU exposure. MNU‐induced prostate/accessory sex gland adenocarcinoma or poorly differentiated carcinoma contained activating mutations in codon 12 of the Ki‐ras oncogene in 80% of primary tumors and in 66% of metastases 633…”
Section: 0 Goalsmentioning
confidence: 99%